2014
DOI: 10.1179/0886963413z.00000000015
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the sagittal condylar inclination: intraindividual variations

Abstract: Results suggest that condylar movement in the sagittal direction is not uniform. Mean left and mean right condylar inclination values do not necessarily describe the actual condylar path, nor do they give adequate information for articulator setup. Left-right side condylar inclination differences greater than 10 degrees can be considered as normal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 30 publications
0
6
0
4
Order By: Relevance
“…Čimić i wsp. 12 wykazali, że średnie nachylenie drogi stawowej w odniesieniu do płaszczyzny frankfurckiej miało wartość ok. 60°. W innym badaniu tego autora, kąty te dla w pełni uzębionych pacjentów wyniosły 40°±27° względem płaszczyzny Campera co stanowi 55°±27° względem frankfurckiej.…”
Section: Omówienie Wyników I Dyskusjaunclassified
See 2 more Smart Citations
“…Čimić i wsp. 12 wykazali, że średnie nachylenie drogi stawowej w odniesieniu do płaszczyzny frankfurckiej miało wartość ok. 60°. W innym badaniu tego autora, kąty te dla w pełni uzębionych pacjentów wyniosły 40°±27° względem płaszczyzny Campera co stanowi 55°±27° względem frankfurckiej.…”
Section: Omówienie Wyników I Dyskusjaunclassified
“…PROTETYKA STOMATOLOGICZNA, 2018; 68, 1 między lewym a prawym kątem nachylenia drogi stawowej były jeszcze wyższe i wyniosły średnio 6-7° (najwyższa wartość różnicy sięgała 22°). 12 Zaledwie 7% pomiarów było identycznych dla obu stawów. 12 W opisanej pracy ułożenie łuku twarzowego było identyczne zarówno podczas manualnego jak i elektronicznego badania, dlatego kąty mierzone tymi metodami można porównać.…”
unclassified
See 1 more Smart Citation
“…Research into the effect of occlusal splint treatment in subjects with bruxism has shown its impact on changes in masticatory muscle activity, the incidence of bruxism, and quality of life. The results of research have shown a change in the range of mandibular movements in subjects with bruxism, however, no studies have been conducted so far regarding the changes in the value of mandibular movements in subjects with bruxism during and after the occlusal splint treatment ( 11 - 13 ). The condyle position in the temporomandibular joint has often been investigated, but as shown by Obrez and Gallo ( 13 ), only through the development of modern kinematic three-dimensional systems with six degrees of freedom it is possible to measure the condyle position and movement mathematically accurately.…”
Section: Introductionmentioning
confidence: 99%
“…The condyle position in the temporomandibular joint has often been investigated, but as shown by Obrez and Gallo ( 13 ), only through the development of modern kinematic three-dimensional systems with six degrees of freedom it is possible to measure the condyle position and movement mathematically accurately. So far, the research in which such devices were used has confirmed that occlusal splint impacts the condyle position in a way that vertical displacement of the condyle between maximum intercuspation (MI) and centric relation (CR) is increased, while the horizontal and transversal condylar displacement show considerable variability ( 11 , 12 ). The objective of this pilot study was to examine the impact of the occlusal splint treatment on mandibular border movements and the condyle position in subjects with bruxism.…”
Section: Introductionmentioning
confidence: 99%